A magnetic fluorescent photonic crystal and its preparation method and application
By combining fluorescent materials into one-dimensional magnetic responsive photonic crystals, the problem of limited optical performance regulation in the prior art is solved, the color and intensity adjustability of optical materials is realized, and the optical performance is enhanced.
Patent Information
- Application Number
- CN202411876533.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-19
AI Technical Summary
In the prior art, one-dimensional magnetically responsive photonic crystal optical materials can only show structural color, and the regulation of optical properties is limited, and there is a lack of research on combining with fluorescent materials.
Magnetic fluorescent photonic crystals are prepared by combining composites with polymerizable substrates. By grafting or adsorbing fluorescent materials on the surface of monodispersed core-shell particles or superparamagnetic nanochain, a new optical material with structural color and fluorescent color is formed.
The color and intensity of optical materials are adjusted, the optical performance is enhanced, and the structural color can be displayed under magnetic field and fluorescent color under excitation light has a wide range of application prospects.
Smart Images

Figure CN119320994B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation of magnetic nano photoelectric materials, and in particular to a magnetic fluorescent photonic crystal and a preparation method and application thereof. Background Art
[0002] Fluorescent materials, as a luminescent material, are widely used due to their bright, stable and non-fading fluorescent colors. They are widely used in biomarkers, displays, medicine and other fields.
[0003] Photonic crystal materials have a unique periodic structure. Due to the existence of photonic band gaps, photonic crystals can control the propagation of light. Responsive photonic crystals can achieve reversible changes in structural color within the visible light range due to their adjustable photonic band gaps, thereby controlling the color and intensity of light. The structural color of one-dimensional magnetically responsive photonic crystals can change with the change of the size and direction of the external magnetic field, or they can be assembled into three-dimensional electrically responsive photonic crystals, and their color and intensity will also change with the change of the electric field size, and this change is reversible. In the process of applying a magnetic field, superparamagnetic nanoparticles are oriented under the action of the magnetic field and assembled into a regular one-dimensional chain structure with periodicity. The lattice spacing of superparamagnetic nanoparticles will change accordingly, thereby controlling the color and intensity of light. Devices or devices prepared by combining fluorescent materials with one-dimensional magnetically responsive photonic crystals can further enrich the regulation of photonic crystals on color and light intensity. The new optical materials combined with the two have unique advantages in the fields of optical information patterns, optical devices, optical elements, optical displays, optical sensors, optical detection, and optical anti-counterfeiting. However, there is no research on the combination of one-dimensional magnetically responsive photonic crystals and fluorescent materials. In addition, the one-dimensional magnetic photonic crystal optical materials currently prepared can only exhibit the color of the photonic crystal structure, and the regulation of optical properties needs to be further improved.
[0004] Therefore, it is necessary to provide a new type of magnetic fluorescent photonic crystal that has both structural color and fluorescent color, which is very necessary for enriching the color and intensity-adjustable magnetic nanophotoelectric materials. Summary of the invention
[0005] In view of this, the present application provides a magnetic fluorescent photonic crystal and a preparation method and application thereof, which are used to enrich the means of regulating the color and intensity of the magnetic photonic crystal.
[0006] In order to achieve the above technical objectives, this application adopts the following technical solutions:
[0007] In a first aspect, the present application provides a magnetic fluorescent photonic crystal, which includes a composite and a polymerizable matrix, wherein the composite includes one or more of a composite of monodisperse core-shell particles and a fluorescent material, a composite of a superparamagnetic nanochain and a fluorescent material, a monodisperse core-shell particle, and a superparamagnetic nanochain. The composite (combination or mixing) methods include: grafting monodisperse core-shell particles or superparamagnetic nanochains onto the surface of fluorescent materials, adsorbing monodisperse core-shell particles or superparamagnetic nanochains onto the surface of fluorescent materials, grafting fluorescent materials onto monodisperse core-shell particles or superparamagnetic nanochains within the core-shell, adsorbing fluorescent materials onto monodisperse core-shell particles or superparamagnetic nanochains within the core-shell, mixing monodisperse core-shell particles or superparamagnetic nanochains without fluorescent materials with polymerizable matrix containing fluorescent materials, mixing monodisperse core-shell particles or superparamagnetic nanochains containing fluorescent materials with polymerizable matrix containing fluorescent materials, mixing monodisperse core-shell particles or superparamagnetic nanochains containing fluorescent materials with polymerizable matrix without fluorescent materials, and chemically combining fluorescent materials with polymerizable matrix containing monodisperse core-shell particles or superparamagnetic nanochains. Due to the unique adjustable photonic band gap structure of photonic crystals, they have structural colors that are different from chemical colors.
[0008] Preferably, the monodisperse core-shell particles include one or more of superparamagnetic nanoparticles@polymer layer, superparamagnetic nanoparticles@silicon dioxide layer, superparamagnetic nanoparticles@polymer layer@silicon dioxide layer, and superparamagnetic nanoparticles with surface coordination, complexation or adsorption of polyhydroxy compounds, and the superparamagnetic nanoparticles contain at least one element of iron, cobalt, and nickel; the particle size of the monodisperse core-shell particles is 60 to 300 nm.
[0009] Preferably, the outer layer of the superparamagnetic nanochain is a silicon dioxide layer and / or a polymer layer, and the inner layer is a single-chain one-dimensional nanostructure composed of monodispersed magnetic cores arranged at equal intervals. The magnetic core contains at least one element of iron, cobalt, and nickel, and the diameter of the superparamagnetic nanochain is 60 to 300 nm.
[0010] In a second aspect, the present application provides a method for preparing a magnetic fluorescent photonic crystal, comprising the following steps:
[0011] S1. preparing monodisperse core-shell particles or superparamagnetic nanochains using superparamagnetic nanoparticles and modified materials as raw materials, wherein the modified materials include one or more of polymer monomers, silica precursors, polyhydroxy compounds, and fluorescent materials;
[0012] S2. Combining the monodisperse core-shell particles or superparamagnetic nanochains with a solution containing a fluorescent material and / or mixing them with a polymerizable matrix containing or not containing a fluorescent material to obtain the magnetic fluorescent photonic crystal.
[0013] Preferably, the fluorescent material includes one or more of fluorescent agents, pigments, dyes, quantum dots, rare earth ion luminescent materials, up-conversion nanoparticles, and phosphorescent objects.
[0014] Preferably, step S1 comprises: using superparamagnetic nanoparticles and one or more substances in a solution containing a polymer monomer, a silica precursor, and a fluorescent material as raw materials, inducing polymerization and / or hydrolysis and condensation under the action of a non-magnetic field, so as to obtain the superparamagnetic nanoparticles @ polymer layer or superparamagnetic nanoparticles @ silica layer or superparamagnetic nanoparticles @ polymer layer @ silica layer containing / not containing fluorescent materials in the shell layer; the inducing polymerization method comprises ultraviolet polymerization and / or thermal polymerization.
[0015] Preferably, step S1 comprises: using superparamagnetic nanoparticles and one or more substances in a solution containing a polymer monomer, a silica precursor, and a fluorescent material as raw materials, inducing polymerization and / or hydrolysis and condensation under the action of a magnetic field, so as to obtain the superparamagnetic nanochain containing / not containing a fluorescent material in the shell layer; the induced polymerization method comprises ultraviolet polymerization and / or thermal polymerization.
[0016] Preferably, the polymer layer formed by the polymer monomer includes a polymer or copolymer containing one or more of an acrylate group, a polyurethane group, an epoxy group, and a urea group.
[0017] Preferably, step S1 comprises: mixing superparamagnetic nanoparticles with polyhydroxy compounds and ultrasonicating to obtain the superparamagnetic nanoparticles with surface coordination, complexation or adsorption of polyhydroxy compounds.
[0018] Preferably, the polyol comprises one or a mixture of tannic acid, catechin, epigallocatechin, epigallocatechin gallate, gluconic acid, glucose, and gluconate.
[0019] Preferably, in step S2, the combining method is: adding a solution containing fluorescent material to monodisperse core-shell particles or superparamagnetic nanochains to react, thereby obtaining the magnetic fluorescent photonic crystal; the solution containing fluorescent material includes fluorescent material, coupling agent, and pH buffer solution.
[0020] Preferably, in step S2, the mixing method is: mixing the polymerizable matrix containing fluorescent material with the monodisperse core-shell particles or superparamagnetic nanochains that do not contain fluorescent material, or mixing the polymerizable matrix containing or not containing fluorescent material with the monodisperse core-shell particles or superparamagnetic nanochains whose shell contains fluorescent and / or surface-bound fluorescent material, so as to obtain the magnetic fluorescent photonic crystal.
[0021] Preferably, the polymerizable matrix is at least one or a mixture of several of epoxy resin, acrylate resin, and polyurethane resin containing or not containing fluorescent material, and is a high-viscosity resin.
[0022] Preferably, in step S2, the polymerizable matrix containing fluorescent material includes mixing or combining the fluorescent material with the matrix; dispersing the monodisperse core-shell particles or superparamagnetic nanochains into a resin, and then mixing with the fluorescent material to obtain the magnetic fluorescent photonic crystal; and / or, mixing the resin, the fluorescent material, and the pH buffer solution to obtain a mixed liquid reaction to obtain a matrix in which the fluorescent material and the high-viscosity resin matrix are chemically combined, and then ultrasonically mixing with the monodisperse core-shell particles or superparamagnetic nanochains to obtain the magnetic fluorescent photonic crystal.
[0023] In a third aspect, the present application provides an optical material of a magnetic fluorescent photonic crystal.
[0024] In a fourth aspect, the present application provides an application method of an optical material, comprising the steps of: obtaining an optical pattern of different colors, intensities and styles by controlling the size and direction of the magnetic field from the magnetic fluorescent photonic crystal, and then fixing the pattern by ultraviolet irradiation or heating; the optical pattern can achieve structural colors that change with angle under visible light, and display fluorescent colors under excitation lighting conditions, and has good application prospects in optical information patterns, optical devices, optical elements, optical displays, optical sensors, optical detection, optical anti-counterfeiting and the like.
[0025] The beneficial effects of this application are as follows:
[0026] The magnetic fluorescent photonic crystal prepared by the preparation method of the present invention includes grafting fluorescent materials on the surface of monodisperse core-shell particles and superparamagnetic nanochains, adsorbing fluorescent materials on the surface of monodisperse core-shell particles and superparamagnetic nanochains, coating fluorescent materials in the shell layer of monodisperse core-shell particles and superparamagnetic nanochains, mixing fluorescent materials in a matrix, and chemically combining fluorescent materials with a matrix. Mainly by means of hydrogen bonding between polymer monomers and the surface of superparamagnetic nanoparticles and between polymer monomers, responsive polymer monomers or their blends are polymerized on the surface of superparamagnetic nanoparticles to form monodisperse core-shell particles or superparamagnetic nanochains, and then fluorescent materials with specific groups are grafted on the surface of monodisperse core-shell particles or superparamagnetic nanochains to achieve the expected effect; or a silicon dioxide layer is first coated on the surface of monodisperse core-shell particles or superparamagnetic nanochains, and then fluorescent materials of corresponding groups are grafted, so that the structure of the chain is more stable and the mechanical strength is greater; or a silicon dioxide layer is directly coated on the surface of superparamagnetic nanoparticles to form monodisperse core-shell particles or superparamagnetic nanochains, and then fluorescent materials of corresponding groups are grafted; or by physical adsorption, The fluorescent material is adsorbed on monodisperse core-shell particles or superparamagnetic nanochains with polymers on the surface; or the fluorescent material is embedded in the shell layer of the monodisperse core-shell particles or superparamagnetic nanochains by an embedding method, which can reduce the influence of the external environment on the fluorescent material; or the monodisperse core-shell particles or superparamagnetic nanochains are mixed with a polymerizable matrix containing the fluorescent material; or the monodisperse core-shell particles or superparamagnetic nanochains containing the fluorescent material are mixed with a polymerizable matrix containing the fluorescent material; or the monodisperse core-shell particles or superparamagnetic nanochains containing the fluorescent material are mixed with a polymerizable matrix not containing the fluorescent material; or the fluorescent material is chemically combined with a high-viscosity resin, and then ultrasonically mixed with the monodisperse core-shell particles or superparamagnetic nanochains, to finally obtain a magnetic fluorescent photonic crystal.
[0027] Compared with existing similar products, the optical pattern prepared by the preparation method of the present invention is composed of magnetic fluorescent photonic crystals, can display corresponding and bright structural colors under a magnetic field and control the color and intensity, can observe obvious angular heterochromia, and can observe more obvious fluorescent colors under the illumination of ultraviolet light or other excitation light. The change between the structural color and the fluorescent color is reversible, and the color is uniform, stable and not easy to fade. It further enriches the regulation of photonic crystals on color and light intensity, improves the optical properties of optical materials, and has relatively broad application prospects in the fields of optical information patterns, optical devices, optical elements, optical displays, optical sensors, optical detection, optical anti-counterfeiting, etc., and can realize a variety of optical information anti-counterfeiting of optical anti-counterfeiting materials in optical anti-counterfeiting. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The fluorescence spectrum of the magnetic fluorescent photonic crystal prepared in Example 1 under a certain excitation light;
[0029] Figure 2The spectrum of the magnetic fluorescent photonic crystal prepared in Example 1 changes with the magnetic field;
[0030] Figure 3 The fluorescence emission peak spectra of the magnetic fluorescent photonic crystal and the initial fluorescent material prepared in Example 1;
[0031] Figure 4 The fluorescence excitation peak spectra of the magnetic fluorescent photonic crystal and the initial fluorescent material prepared in Example 1;
[0032] Figure 5 This is a fluorescence microscope image of the magnetic fluorescent photonic crystal prepared in Example 1;
[0033] Figure 6 is a scanning electron microscope image of the magnetic fluorescent photonic crystal prepared in Example 1;
[0034] Figure 7 The figure is a comparison of the physical images of the magnetic fluorescent photonic crystal prepared in Example 1;
[0035] Figure 8 The fluorescence spectrum of the magnetic fluorescent photonic crystal prepared in Example 2 under a certain excitation light;
[0036] Fig. 9 The fluorescence emission peak spectra of the magnetic fluorescent photonic crystal and the initial fluorescent material prepared in Example 2;
[0037] Fig.10 The fluorescence excitation peak spectra of the magnetic fluorescent photonic crystal and the initial fluorescent material prepared in Example 2;
[0038] Fig.11 This is an optical microscope image of the magnetic fluorescent photonic crystal prepared in Example 3;
[0039] Fig.12 The fluorescence spectrum of the magnetic fluorescent photonic crystal prepared in Example 3 under a certain excitation light;
[0040] Fig.13 The fluorescence spectrum of the magnetic fluorescent photonic crystal prepared in Example 4 under a certain excitation light;
[0041] Fig.14 The fluorescence spectrum of the magnetic fluorescent photonic crystal prepared in Example 5 under a certain excitation light;
[0042] Fig.15 The spectrum of the magnetic fluorescent photonic crystal prepared in Example 5 changes with the magnetic field;
[0043] Fig.16 is a scanning electron microscope image of the magnetic fluorescent photonic crystal prepared in Example 5;
[0044] Fig.17 The fluorescence spectrum of the magnetic fluorescent photonic crystal prepared in Example 6 under a certain excitation light;
[0045] Fig.18 The fluorescence spectrum of the magnetic fluorescent photonic crystal prepared in Example 7 under a certain excitation light;
[0046] Fig.19 The fluorescence spectrum of the magnetic fluorescent photonic crystal prepared in Example 8 under a certain excitation light;
[0047] Fig. 20 The fluorescence spectrum of the magnetic fluorescent photonic crystal prepared in Example 9 under a certain excitation light;
[0048] Fig.21 The fluorescence spectrum of the magnetic fluorescent photonic crystal prepared in Example 10 under a certain excitation light;
[0049] Fig. 22 The fluorescence spectrum of the magnetic fluorescent photonic crystal prepared in Example 11 under a certain excitation light;
[0050] Fig.23 The fluorescence spectrum of the magnetic fluorescent photonic crystal prepared in Example 12 under a certain excitation light;
[0051] Fig.24 Spectral comparison diagram of the magnetic fluorescent photonic crystal prepared in Example 13 and the magnetic photonic crystal without mixed fluorescence;
[0052] Fig.25 The fluorescence spectrum of the magnetic fluorescent photonic crystal prepared in Example 14 under a certain excitation light;
[0053] Fig.26 The spectrum of the magnetic fluorescent photonic crystal optical material prepared in Example 15 under a magnetic field varies with the magnetic field strength;
[0054] Fig. 27 This is a physical picture of the optical pattern prepared in Example 15;
[0055] Fig.28 The spectrum of the magnetic fluorescent photonic crystal optical material prepared in Example 16 under a magnetic field varies with the intensity of the magnetic field;
[0056] Fig.29 This is a graph showing the change in peak position of the magnetic fluorescent photonic crystal optical material prepared in Example 16 at different observation angles;
[0057] Fig.30 This is a physical picture of the optical pattern prepared in Example 16; DETAILED DESCRIPTION
[0058] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0059] The present application provides a magnetic fluorescent photonic crystal, which includes a composite and a polymerizable matrix, wherein the composite includes one or more of a composite of monodisperse core-shell particles and fluorescent materials, a composite of superparamagnetic nanochains and fluorescent materials, monodisperse core-shell particles, and superparamagnetic nanochains. The combination or mixing methods include: grafting monodisperse core-shell particles or superparamagnetic nanochains onto the surface of fluorescent materials, adsorbing monodisperse core-shell particles or superparamagnetic nanochains onto the surface of fluorescent materials, grafting fluorescent materials onto monodisperse core-shell particles or superparamagnetic nanochains within the core-shell, adsorbing fluorescent materials onto monodisperse core-shell particles or superparamagnetic nanochains within the core-shell, mixing monodisperse core-shell particles or superparamagnetic nanochains with a polymerizable matrix containing fluorescent materials, mixing monodisperse core-shell particles or superparamagnetic nanochains containing fluorescent materials with a polymerizable matrix containing fluorescent materials, mixing monodisperse core-shell particles or superparamagnetic nanochains containing fluorescent materials with a polymerizable matrix not containing fluorescent materials, and chemically combining fluorescent materials with a matrix containing monodisperse core-shell particles or superparamagnetic nanochains. Due to the unique adjustable photonic band gap structure of photonic crystals, they have structural colors that are different from chemical colors.
[0060] The monodisperse core-shell particles include one or more of superparamagnetic nanoparticles@polymer layer, superparamagnetic nanoparticles@silicon dioxide layer, superparamagnetic nanoparticles@polymer layer@silicon dioxide layer, and superparamagnetic nanoparticles with surface coordination, complexation or adsorption of polyhydroxy compounds. The superparamagnetic nanoparticles contain at least one element of iron, cobalt, and nickel. The particle size of the monodisperse core-shell particles is 60 to 300 nm.
[0061] The outer layer of the superparamagnetic nanochain is a silicon dioxide layer and / or a polymer layer, and the inner layer is a single-chain one-dimensional nanostructure composed of monodispersed magnetic cores arranged at equal intervals. The magnetic core contains at least one element of iron, cobalt, and nickel. The diameter of the superparamagnetic nanochain is 60 to 300 nm.
[0062] The monodisperse core-shell particles or superparamagnetic nanochains are modified with active functional groups, including but not limited to hydroxyl groups and carboxyl groups. In some embodiments, the polymer layer is connected to the silica layer through hydrogen bonds, and the fluorescent material is grafted to the polymer layer through hydroxyl-carboxyl, amino-carboxyl and other interactions using its own chemical groups. The fluorescent material is grafted to the silica layer through isothiocyanate-amino, carboxyl-amino, sulfonic acid-amino and other interactions using a silane coupling agent.
[0063] The present application provides a method for preparing a magnetic fluorescent photonic crystal, comprising the following steps:
[0064] S1. preparing monodisperse core-shell particles or superparamagnetic nanochains using superparamagnetic nanoparticles and modified materials as raw materials, wherein the modified materials include one or more of polymer monomers, silica precursors, polyhydroxy compounds, and fluorescent materials;
[0065] S2. Combining the monodisperse core-shell particles or superparamagnetic nanochains with a solution containing a fluorescent material and / or mixing them with a polymerizable matrix containing or not containing a fluorescent material to obtain the magnetic fluorescent photonic crystal.
[0066] In some embodiments, monodisperse core-shell particles or superparamagnetic nanochains are dispersed in a high viscosity resin matrix and mixed with a fluorescent material; or the fluorescent material is chemically combined with a high viscosity resin matrix and then mixed with monodisperse core-shell particles or superparamagnetic nanochains to obtain the magnetic fluorescent photonic crystal.
[0067] Preferably, step S1 comprises: uniformly mixing superparamagnetic nanoparticles with polymer monomers, crosslinking agents, initiators and dispersion medium solvents to obtain a uniform prepolymer solution, and inducing polymerization of the prepolymer solution under the action of a non-magnetic field to obtain a superparamagnetic nanoparticle@polymer layer; the inducing polymerization method comprises ultraviolet polymerization and / or thermal polymerization.
[0068] The concentration of superparamagnetic nanoparticles in the prepolymer solution is 0.1-4 mg / ml. If the concentration is too low, the yield will be too small. If the concentration is too high, the product will have poor color or even aggregate to form a gel.
[0069] The polymer monomers include one or more of acrylic acid, hydroxyethyl methacrylate, acrylamide, methacrylic acid, methyl methacrylate, ethyl methacrylate, N-isopropylacrylamide and N-isopropylmethacrylamide. The concentration of the polymer monomers in the prepolymer solution is 0.05-1.0 mmol / ml.
[0070] The crosslinking agent is one or more of ethylene glycol dimethacrylate, methylene bisacrylamide or diisocyanate, and the molar content of the crosslinking agent is 1%-10% of the total molar amount of the polymer monomers. The dispersion medium solvent is a mixture of water and ethylene glycol; the initiator is one of 2-hydroxy-2-methyl-1-phenylacetone, 1-hydroxycyclohexyl phenyl ketone, azobisisobutyl cyanide, diacyl peroxide or persulfate, and the molar content of the initiator is 0.1%-5% of the total molar amount of the polymer monomers.
[0071] The fluorescent material of the present application includes one or more of fluorescent agents, pigments, dyes, quantum dots, rare earth ion luminescent materials, upconversion nanoparticles, and phosphorescent objects. The selected fluorescent materials can be modified by themselves or coupling agents and connected with carboxyl groups or hydroxyl groups, and are all within the protection scope of the present application; in some embodiments, the fluorescent material has one or more of amino, hydroxyl, isothiocyanate, epoxy, quaternary ammonium salt, imino, and carbonyl groups; the fluorescent materials include but are not limited to rhodamine B, rhodamine 110, 5-carboxyfluorescein, rhodamine 123, 5(6)-aminofluorescein, 4,5-diaminofluorescein yellow, 4,5-diaminofluorescein diacetate, 5-(N-hexadecanoyl)aminofluorescein Yellow, 5-(4,6-dichlorotriazine)aminofluorescein, 2-aminoacridone, 8-hydroxy-1,3,6-pyrenetrisulfonic acid trisodium, salicylfluorescein, 4,5-dihydroxyfluorescein yellow, fluorescein isothiocyanate, rhodamine isothiocyanate B, 5-fluorescein isothiocyanate cadaverine, quantum dot fluorescence, rare earth materials, 6-carboxyfluorescein, cyanine dyes, n-phenylnaphthylamine, fluorescein isothiocyanate, 6-carboxy-4',5'-dichloro-2',7'-dimethoxyfluorescein; the excitation wavelength of the fluorescent material is 365-750nm, the maximum emission wavelength is 450-773nm, and the content of the fluorescent material in the magnetic fluorescent photonic crystal is 0.001-1mmol / L.
[0072] Preferably, step S1 comprises: using superparamagnetic nanoparticles and a solution of polymer monomers, crosslinking agents, initiators and / or catalysts, and a silicon source as raw materials, inducing polymerization under the action of a magnetic field to obtain superparamagnetic nanochains, or adding fluorescent materials, coupling agents, and pH buffer solutions during the polymerization process to obtain superparamagnetic nanochains containing fluorescence in the shell, and the inducing polymerization method comprises ultraviolet polymerization and / or thermal polymerization; the magnetic field intensity when inducing polymerization under a magnetic field environment is 70Gs-400Gs.
[0073] Preferably, step S1 comprises: using superparamagnetic nanoparticles, a catalyst, a silicon source and as raw materials, and reacting by a sol-gel method to obtain a superparamagnetic nanoparticle@silicon dioxide layer.
[0074] Preferably, step S1 comprises: using superparamagnetic nanoparticles@polymer layer, catalyst, and silicon source as raw materials, and reacting by sol-gel method to obtain superparamagnetic nanoparticles@polymer layer@silicon dioxide layer.
[0075] Preferably, step S1 comprises: adding fluorescent material, coupling agent, and pH buffer during the polymerization / hydrolysis and condensation process to obtain monodisperse core-shell particles containing fluorescence in the shell layer.
[0076] In the sol-gel method, the catalyst is ammonia water, and the amount of the catalyst is 0.5%-10% of the total volume of the reaction system; the silicon source is one or more of ethyl orthosilicate, tetramethyl silicate and propyl silicate, and the amount of the silicon source is 0.5%-10% of the total volume of the reaction system; the temperature is 20-60°C; and the stirring speed is 100-400r / min.
[0077] Preferably, step S1 comprises: mixing superparamagnetic nanoparticles with polyhydroxy compounds and ultrasonicating to obtain superparamagnetic nanoparticles with surface coordination, complexation or adsorption of polyhydroxy compounds.
[0078] In step S1, the polyol comprises one or a mixture of tannic acid, catechin, epigallocatechin, epigallocatechin gallate, gluconic acid, glucose, and gluconate.
[0079] Preferably, in step S2, the combining method is: mixing the fluorescent material, coupling agent, and pH buffer solution to obtain a mixed solution, and then dropping the mixed solution into monodisperse core-shell particles or superparamagnetic nanochains containing or not containing fluorescent materials in the shell layer to react, thereby obtaining a magnetic fluorescent photonic crystal.
[0080] In step S2, the process conditions for grafting the monodisperse core-shell particles or superparamagnetic nanochains with the fluorescent material are: a rotation speed of 200-500 r / min, a mixed solvent of ethanol and / or water, and a reaction temperature of 20-60°C.
[0081] In step S2, the coupling agent is an amino-containing coupling agent, including but not limited to one or more of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-β (aminoethyl)-γ-aminopropyltrimethoxysilane, N-β (aminoethyl)-γ-aminopropyldimethoxysilane, N-β (aminoethyl)-γ-aminopropyltriethoxysilane, N-β (aminoethyl)-γ-aminopropyldiethoxysilane, anilinomethyltrimethoxysilane, and aminoethylaminoethylaminopropyltrimethoxysilane, and the amount of the coupling agent is 0.01%-0.5% of the total volume of the prepolymer solution; the pH buffer solution includes but is not limited to one or more of a phosphate buffer solution, a borate buffer solution, and a hydrochloric acid buffer solution, and the pH buffer solution accounts for 0.5%-5% of the total volume of the prepolymer solution.
[0082] Preferably, in step S2, the mixing method is: mixing the polymerizable matrix containing the fluorescent material with the monodisperse core-shell particles or superparamagnetic nanochains that do not contain the fluorescent material, or mixing the polymerizable matrix containing or not containing the fluorescent material with the monodisperse core-shell particles or superparamagnetic nanochains whose shell contains fluorescent and / or surface-bound fluorescent materials, so as to obtain the magnetic fluorescent photonic crystals.
[0083] In some embodiments, a high viscosity resin, a fluorescent material, and a pH buffer solution are mixed and reacted to obtain a matrix in which the fluorescent material and the high viscosity resin are chemically combined, and then ultrasonically mixed with monodisperse core-shell particles or superparamagnetic nanochains containing or not containing the fluorescent material to obtain the magnetic fluorescent photonic crystal.
[0084] In some embodiments, the process conditions for chemically combining the fluorescent material with the high-viscosity resin matrix are: mechanical stirring, a rotation speed of 300-600 r / min, and a temperature of 20-60°C.
[0085] In some embodiments, the pH buffer includes, but is not limited to, one or more of a phosphate buffer solution, a borate buffer solution, and a hydrochloric acid buffer solution, and the pH buffer accounts for 0.5%-5% of the total volume of the prepolymer solution.
[0086] In a third aspect, the present application provides an optical material comprising a magnetic fluorescent photonic crystal; the optical material comprises a magnetic fluorescent photonic crystal, a polymerizable matrix or a magnetic photonic crystal and a fluorescent-doped polymerizable matrix; the polymerizable matrix comprises a resin or a fluorescent-doped resin and a photoinitiator, wherein the resin comprises at least one of an epoxy resin, an acrylate resin, and a polyurethane resin.
[0087] In a fourth aspect, the present application provides an application method of an optical material, comprising the steps of: obtaining an optical pattern of different colors, intensities and styles by controlling the size and direction of a magnetic field through the optical material, and then fixing the pattern by ultraviolet irradiation or heating; the optical pattern can achieve structural colors that change with angle under visible light, and display fluorescent colors under excitation lighting conditions, and has good application prospects in optical information patterns, optical devices, optical elements, optical displays, optical sensors, optical detection, optical anti-counterfeiting and the like.
[0088] The present solution is further described below through specific embodiments.
[0089] Example 1
[0090] A magnetic fluorescent photonic crystal, comprising a combination of a superparamagnetic nanochain and a fluorescent material, wherein the outer layer of the superparamagnetic nanochain is a silicon dioxide layer;
[0091] The superparamagnetic nanochains are obtained by mixing superparamagnetic ferroferric oxide nanoparticles, polymer monomers, crosslinking agents, photoinitiators, and dispersion medium solvents to form a prepolymer solution, which is then cured by ultraviolet polymerization under the action of a magnetic field; the polymer monomers include hydroxyethyl methacrylate (HEMA) and acrylic acid (AA), the crosslinking agent is ethylene glycol dimethacrylate (EGDMA), the photoinitiator is 2-hydroxy-2-methyl-1-phenylpropanone (HMPP), and the dispersion medium solvents are ethylene glycol and water; the modified fluorescent material is fluorescein isothiocyanate (FITC) combined with γ-aminopropyltriethoxysilane.
[0092] Under the action of a magnetic field, the superparamagnetic nanochain is a one-dimensional chain structure formed by connecting and coating superparamagnetic ferroferric oxide nanoparticles through the action of polymer monomers and cross-linking agents. Silica is coated on the surface of the superparamagnetic nanochain through hydrogen bonding. With a coupling agent as a bridge, the silanol on the surface of the silica is connected to the methyl end of the coupling agent through hydrolysis condensation, while the other end is connected to the silica layer and the fluorescent material through the action of the amino-isothiocyanate group.
[0093] The preparation steps of magnetic fluorescent photonic crystals are as follows:
[0094] Dispersing superparamagnetic ferroferric oxide nanoparticles into a prepolymer solution composed of hydroxyethyl methacrylate (HEMA), acrylic acid (AA), crosslinking agent ethylene glycol dimethacrylate (EGDMA), photoinitiator 2-hydroxy-2-methyl-1-phenylpropanone (HMPP), ethylene glycol and water, the concentration of HEMA monomer is 0.205mmol / ml, the concentration of AA monomer is 0.309mmol / ml, the amount of EGDMA is 8% of the total molar amount of HEMA and AA monomers, the amount of HMPP is 2% of the total molar amount of HEMA and AA monomers, the concentration of superparamagnetic nanoparticles in the prepolymer solution is 0.64mg / ml, and the volume ratio of ethylene glycol to water is 3:1; placing the prepolymer solution in a magnetic field of 180Gs for magnetization for 3min, keeping the magnetic field unchanged, and irradiating it with ultraviolet light for 5min to obtain a photonic nanochain, repeatedly washing it with ethanol, centrifuging it 2-3 times, and finally dispersing it in ethanol;
[0095] The obtained photonic nanochains were mixed evenly with ammonia water, tetraethyl orthosilicate (TEOS), ethanol and water, wherein the volume fraction of ammonia water was 2.5%, the volume fraction of TEOS was 4.2%, and the ratio of ethanol to water was 10:1; the mixed solution was placed in a 30°C water bath and stirred for 30 minutes to obtain the silica-coated photonic nanochains, and after the reaction was completed, the mixture was washed with ethanol, centrifuged several times, and finally dispersed in ethanol;
[0096] The silica-coated photonic nanochains were mixed evenly with phosphate buffer solution (PBS) and fluorescein isothiocyanate (FITC) bound to γ-aminopropyltriethoxysilane in ethanol, PBS accounted for 0.96% of the whole solution, and the concentration of FITC in the solution was 0.045mmol / L. The mixed solution was placed in a 40℃ water bath and stirred for 1.5h to obtain fluorescently modified photonic nanochains. After the reaction, the solution was washed with ethanol and centrifuged several times, and the final product was dispersed in epoxy resin.
[0097] Figure 1 The fluorescence spectrum of the product obtained in Example 1 shows that the product has a relatively obvious fluorescence intensity under a certain excitation light; Figure 2This is a spectrum diagram of the product obtained in Example 1 under a magnetic field. It can be seen that when the magnetic field changes from 200-600Gs, the reflectivity hardly changes; Figure 3 and Figure 4 The fluorescence emission spectrum and fluorescence excitation spectrum of the product obtained in Example 1 are compared with the emission spectrum and excitation spectrum of the initial fluorescent material. It can be seen that the emission peak of the fluorescent material after combining with the photonic crystal is red-shifted from 520nm to 536nm, the excitation peak is red-shifted from 487nm to 527nm, and a new excitation peak is generated at 444nm, indicating that the special structure of the photonic crystal has a regulating effect on the color of the fluorescent material; Figure 5 and Figure 6 The fluorescence microscope pictures and scanning electron microscope pictures of the product obtained in Example 1 show that the length of the photonic nanochains is mostly within 10 μm and the chains exhibit strong green fluorescence. The outer layer of the chains is coated with a layer of silicon dioxide core-shell structure with a thickness of about 30 nm. Figure 7 This is a comparison of the physical picture of the product obtained in Example 1 when ultraviolet excitation light is applied. The left picture is a physical picture of the product grafted with fluorescent material, and the right picture is a physical picture without adding fluorescent material.
[0098] Example 2
[0099] A magnetic fluorescent photonic crystal, comprising a combination of a superparamagnetic nanochain and a fluorescent material, wherein the outer layer of the superparamagnetic nanochain is a silicon dioxide layer;
[0100] The superparamagnetic nanochains are prepared by mixing superparamagnetic cobalt oxide nanoparticles, a silicon source, a catalyst and a dispersion medium solvent to form a prepolymer solution. Under the action of a magnetic field, silicon dioxide obtained by hydrolysis and condensation is coated on the surface of the superparamagnetic cobalt oxide nanoparticles through hydrogen bonding. Due to the presence of the magnetic field, superparamagnetic nanochains with silicon dioxide on the surface are formed. The silicon source is tetraethyl orthosilicate (TEOS), the catalyst is ammonia water, and the dispersion medium solvent is ethanol and water. The modified fluorescent material is rhodamine B isothiocyanate (RBITC) combined with N-β (aminoethyl)-γ-aminopropyltrimethoxysilane.
[0101] Under the action of a magnetic field, the superparamagnetic nanochain is a one-dimensional chain structure formed by superparamagnetic cobalt oxide nanoparticles connected and coated by the action of silica. The silica is coated on the surface of the superparamagnetic nanochain through hydrogen bonding, and the surface of the superparamagnetic nanochain has hydroxyl groups. With a coupling agent as a bridge, the silanol on the surface of the silica is connected to the methyl end of the coupling agent through hydrolysis condensation, and the other end is connected to the silica layer and the fluorescent material through the action of the amino-isothiocyanate group.
[0102] The preparation steps of magnetic fluorescent photonic crystals are as follows:
[0103] Superparamagnetic cobalt oxide nanoparticles are dispersed in a prepolymer solution composed of tetramethyl silicate, ammonia water, ethanol and water, wherein the volume fraction of ammonia water is 2%, the volume fraction of tetramethyl silicate is 3.9%, the ratio of ethanol to water is 20:1, and the concentration of superparamagnetic nanoparticles in the prepolymer solution is 0.64 mg / ml; the prepolymer solution is placed in a magnetic field of 200 Gs and magnetized for 30 minutes while keeping the magnetic field unchanged to obtain a photonic nanochain, which is repeatedly washed with ethanol and centrifuged 2-3 times, and finally dispersed in ethanol.
[0104] The silica-coated photonic nanochains were mixed evenly with borate buffer solution (BBS) and rhodamine isothiocyanate B (RBITC) bound to N-β (aminoethyl)-γ-aminopropyltrimethoxysilane in ethanol, BBS accounted for 0.5% of the whole solution, the concentration of RBITC in the solution was 0.104mmol / L, the ratio of ethanol to water was 20:1, and the mixture was placed in a 40°C water bath and stirred for 3h to obtain fluorescently modified photonic nanochains. After the reaction, the mixture was washed with ethanol and centrifuged several times, and the final product was dispersed in acrylic resin.
[0105] Figure 8 The fluorescence spectrum of the product obtained in Example 2 shows that the product has a relatively obvious fluorescence intensity under an excitation light of a certain wavelength; Fig. 9 and Fig.10 The fluorescence emission spectrum and fluorescence excitation spectrum of the product obtained in Example 2 are compared with the emission spectrum and excitation spectrum of the initial fluorescent material. It can be seen that the emission peak of the fluorescent material after combining with the photonic crystal is blue-shifted from 601nm to 584nm, and the excitation peak is blue-shifted from 592nm to 578nm, indicating that the special structure of the photonic crystal has a regulating effect on the color of the fluorescent material.
[0106] Example 3
[0107] A magnetic fluorescent photonic crystal, comprising a combination of a superparamagnetic nanochain and a fluorescent material, wherein the outer layer of the superparamagnetic nanochain is a silicon dioxide layer;
[0108] The superparamagnetic nanochains are obtained by mixing superparamagnetic NiFe2O4 nanoparticles, polymer monomers, crosslinking agents, photoinitiators, and dispersion medium solvents to form a prepolymer solution, which is then cured by ultraviolet polymerization under the action of a magnetic field; the polymer monomers include acrylic acid (AA), the crosslinking agent is bisacrylamide (BIS), the photoinitiator is ammonium persulfate (APS), and the dispersion medium solvents are ethylene glycol and water; the modified fluorescent material is Cy3 combined with γ-aminopropyltriethoxysilane.
[0109] Under the action of a magnetic field, the superparamagnetic nanochain is a one-dimensional chain structure formed by connecting and coating superparamagnetic NiFe2O4 nanoparticles through the action of polymer monomers and cross-linking agents, and silica is coated on the surface of the superparamagnetic nanochain through hydrogen bonding; using a coupling agent as a bridge, the silanol on the surface of silica is connected to the methyl end of the coupling agent through hydrolysis condensation, and the other end is amino-modified by the coupling agent through the action of the amino-sulfonic acid group, and the silica layer is connected to the fluorescent material.
[0110] The preparation steps of magnetic fluorescent photonic crystals are as follows:
[0111] Superparamagnetic NiFe2O4 nanoparticles are dispersed in a solution consisting of acrylic acid (AA), crosslinking agent bisacrylamide (BIS), initiator ammonium persulfate (APS), ethylene glycol and water, the concentration of AA monomer is 0.309mmol / ml, the amount of BIS is 6% of the molar amount of AA monomer, the amount of APS is 2% of the molar amount of AA monomer, the concentration of monodisperse superparamagnetic nanoparticles in the prepolymer solution is 0.5mg / ml, and the volume ratio of ethylene glycol to water is 3:1; the prepolymer solution is placed in a magnetic field of 250Gs and magnetized for 3min, the magnetic field is kept unchanged, and the reaction is carried out at 45°C for 5min to obtain a photonic nanochain, which is repeatedly washed with ethanol and centrifuged 2-3 times, and finally dispersed in ethanol.
[0112] The obtained photonic nanochains were evenly mixed with ammonia water, propyl silicate, ethanol and water, with the volume fraction of ammonia water being 3.3%, the volume fraction of propyl silicate being 5%, and the ratio of ethanol to water being 10:1; the mixed solution was placed in a 30°C water bath and stirred for 30 minutes to obtain silica-coated photonic nanochains. After the reaction was completed, the mixture was washed with ethanol, centrifuged several times, and finally dispersed in ethanol.
[0113] The silica-coated photonic nanochains were mixed evenly with hydrochloric acid buffer solution (Tris) and Cy3 bound to γ-aminopropyltriethoxysilane in ethanol, Tris accounted for 3% of the whole solution, and the concentration of Cy3 in the solution was 0.0425mmol / L. The mixed solution was placed in a 50°C water bath and stirred for 1.5h to obtain the fluorescently modified photonic nanochains. After the reaction, the solution was washed with ethanol and centrifuged several times. The final product was dispersed in epoxy resin.
[0114] Fig.11 This is an optical microscope picture of the product obtained in Example 3. From the picture, it can be seen that the chain flexibility of 6% cross-linking degree is greater; Fig.12 This is the fluorescence spectrum of the product obtained in Example 3. It can be seen from the figure that the product has a relatively obvious fluorescence intensity under an excitation light of a certain wavelength.
[0115] Example 4
[0116] A magnetic fluorescent photonic crystal, comprising a combination of a superparamagnetic nanochain and a fluorescent material, wherein the outer layer of the superparamagnetic nanochain is a silicon dioxide layer;
[0117] The superparamagnetic nanochains are prepared by mixing superparamagnetic CoNiFe2O4 nanoparticles, polymer monomers, crosslinking agents, photoinitiators and dispersion medium solvents to form a prepolymer solution, which is then cured by ultraviolet polymerization under the action of a magnetic field. The polymer monomers include hydroxyethyl methacrylate (HEMA) and acrylic acid (AA), the crosslinking agent is ethylene glycol dimethacrylate (EGDMA), the photoinitiator is 2-hydroxy-2-methyl-1-phenylpropanone (HMPP), and the dispersion medium solvents are ethylene glycol and water. The fluorescent material is rhodamine 110 (Rh 110).
[0118] Under the action of a magnetic field, the superparamagnetic nanochain is a one-dimensional chain structure formed by connecting and coating superparamagnetic CoNiFe2O4 nanoparticles through polymer monomers and cross-linking agents. Silica is coated on the surface of the superparamagnetic nanochain through hydrogen bonds; the fluorescent material is connected to the silicon hydroxyl groups of the silica layer through its own carboxyl groups.
[0119] The preparation steps of magnetic fluorescent photonic crystals are as follows:
[0120] The superparamagnetic CoNiFe2O4 nanoparticles are dispersed in a prepolymer solution composed of hydroxyethyl methacrylate (HEMA), acrylic acid (AA), crosslinking agent ethylene glycol dimethacrylate (EGDMA), photoinitiator 2-hydroxy-2-methyl-1-phenylpropanone (HMPP), ethylene glycol and water, the concentration of HEMA monomer is 0.304mmol / ml, the concentration of AA monomer is 0.5mmol / ml, the amount of EGDMA is 8% of the total molar amount of HEMA and AA monomers, the amount of HMPP is 2% of the molar amount of HEMA and AA monomers, the concentration of superparamagnetic nanoparticles in the solution is 1.2mg / ml, and the volume ratio of ethylene glycol to water is 5:2; the prepolymer solution is placed in a magnetic field of 160Gs for magnetization for 3min, the magnetic field is kept unchanged, and ultraviolet light is irradiated for 5min to obtain a photonic nanochain, which is repeatedly washed with ethanol and centrifuged 2-3 times, and finally dispersed in ethanol.
[0121] The obtained photonic nanochains were evenly mixed with ammonia water, tetraethyl orthosilicate (TEOS), ethanol and water, with the volume fraction of ammonia water being 0.8%, the volume fraction of TEOS being 2%, and the ratio of ethanol to water being 5:1; the mixed solution was placed in a 40°C water bath and stirred for 30 minutes to obtain silica-coated photonic nanochains. After the reaction was completed, the mixture was washed with ethanol, centrifuged several times, and finally dispersed in ethanol.
[0122] The silica-coated photonic nanochains were mixed evenly with phosphate buffer solution (PBS) and rhodamine 110 (Rh 110) in ethanol, with PBS accounting for 1% of the whole solution and the concentration of Rh 110 in the solution being 0.025 mmol / L. The mixed solution was placed in a 40°C water bath and stirred for 2 h to obtain fluorescently modified photonic nanochains. After the reaction, the mixture was washed with ethanol and centrifuged several times, and the final product was dispersed in epoxy resin.
[0123] Fig.13 This is the fluorescence spectrum of the product obtained in Example 4. It can be seen from the figure that the product has a relatively obvious fluorescence intensity under an excitation light of a certain wavelength.
[0124] Example 5
[0125] A magnetic fluorescent photonic crystal, comprising a combination of monodisperse core-shell particles and a fluorescent material, wherein the monodisperse core-shell particles are superparamagnetic nanoparticles@polymer layer@silicon dioxide layer;
[0126] The superparamagnetic nanoparticles@polymer layer is prepared by mixing superparamagnetic ferroferric oxide nanoparticles, polymer monomers, crosslinking agents, photoinitiators, and dispersion medium solvents to form a prepolymer solution, and then curing the prepolymer solution by ultraviolet polymerization under the action of a non-magnetic field, so that the polymer monomers form a polymer that is coated on the surface of the superparamagnetic nanoparticles; the polymer monomers include hydroxyethyl methacrylate (HEMA) and acrylic acid (AA), the crosslinking agent is ethylene glycol dimethacrylate (EGDMA), the photoinitiator is 2-hydroxy-2-methyl-1-phenylpropanone (HMPP), and the dispersion medium solvents are ethylene glycol and water; the modified fluorescent material is fluorescein isothiocyanate (FITC) combined with γ-aminopropyltriethoxysilane.
[0127] Under the action of non-magnetic field, polymer monomers are coated on the surface of superparamagnetic iron oxide nanoparticles, and silicon dioxide is coated on the surface of superparamagnetic nanoparticles through hydrogen bonding; using the coupling agent as a bridge, the silanol group on the surface of silicon dioxide and the methyl end of the coupling agent are connected by hydrolysis condensation, and the other end is connected to the silicon dioxide layer and the fluorescent material through the action of the amino-isothiocyanate group.
[0128] The preparation method of magnetic fluorescent photonic crystal is as follows:
[0129] Superparamagnetic ferroferric oxide nanoparticles are dispersed in a prepolymer solution consisting of hydroxyethyl methacrylate (HEMA), acrylic acid (AA), crosslinking agent ethylene glycol dimethacrylate (EGDMA), photoinitiator 2-hydroxy-2-methyl-1-phenylpropanone (HMPP), ethylene glycol and water, the concentration of HEMA monomer is 0.205 mmol / ml, the concentration of AA monomer is 0.309 mmol / ml, the amount of EGDMA and HMPP is 2% of the total molar amount of HEMA and AA monomers, the concentration of superparamagnetic nanoparticles in the prepolymer solution is 0.64 mg / ml, and the volume ratio of ethylene glycol to water is 3:1; after irradiating the prepolymer solution with ultraviolet light for 5 minutes, it is repeatedly washed with ethanol and centrifuged 2-3 times, and finally the product is dispersed in ethanol.
[0130] The obtained product was evenly mixed with ammonia water, tetraethyl orthosilicate (TEOS), ethanol and water, the volume fraction of ammonia water was 0.88%, the volume fraction of TEOS was 2.65%, and the ratio of ethanol to water was 10:1; the mixed solution was placed in a 30°C water bath and stirred for 30 minutes to obtain superparamagnetic nanoparticles @ polymer layer @ silica layer. After the reaction was completed, it was washed with ethanol, centrifuged several times, and finally dispersed in ethanol.
[0131] Superparamagnetic nanoparticles@polymer layer@silica layer, phosphate buffer solution (PBS), and fluorescein isothiocyanate (FITC) bound to γ-aminopropyltriethoxysilane are mixed evenly in ethanol, PBS accounts for 0.95% of the whole solution, and the concentration of FITC in the solution is 0.036mmol / L. The mixed solution is placed in a 40℃ water bath and stirred for 1.5h to obtain fluorescently modified superparamagnetic nanoparticles. After the reaction is completed, it is washed with ethanol and centrifuged several times. The final product is dispersed in epoxy resin.
[0132] Fig.14 The fluorescence spectrum of the product obtained in Example 5 shows that the product has a relatively obvious fluorescence intensity under a certain excitation light; Fig.15 This is a spectrum diagram of the product obtained in Example 5 under a magnetic field. When the applied magnetic field changes from 200 Gs to 1000 Gs, the peak position and light intensity of the magnetic fluorescent photonic crystal gradually change with the change of the magnetic field; Fig.16 This is a scanning electron microscope image of the product obtained in Example 5. It can be seen that the superparamagnetic nanoparticles have a smooth outer layer, the particle size is mostly within 200nm, and are covered with a very thin SiO2 shell.
[0133] Example 6
[0134] A magnetic fluorescent photonic crystal, comprising a combination of monodisperse core-shell particles and a fluorescent material, wherein the monodisperse core-shell particles are superparamagnetic nanoparticles@polymer layer;
[0135] The superparamagnetic nanoparticles@polymer layer is prepared by mixing superparamagnetic ferroferric oxide nanoparticles, polymer monomers, crosslinking agents, photoinitiators, and dispersion medium solvents to form a prepolymer solution, and then curing the prepolymer solution by ultraviolet polymerization in the absence of a magnetic field. The polymer monomers form a polymer that is coated on the surface of the superparamagnetic nanoparticles. The polymer monomers include hydroxyethyl methacrylate (HEMA) and acrylic acid (AA), the crosslinking agent is ethylene glycol dimethacrylate (EGDMA), the photoinitiator is 2-hydroxy-2-methyl-1-phenylpropanone (HMPP), and the dispersion medium solvents are ethylene glycol and water. The fluorescent material is 5-aminofluorescein (AF).
[0136] Under the action of non-magnetic field, the polymer monomer is coated on the surface of superparamagnetic ferroferric oxide nanoparticles, and the superparamagnetic nanoparticles@polymer layer is provided with carboxyl groups; the fluorescent material is coupled with the superparamagnetic nanoparticles@polymer layer through its own amino groups.
[0137] The preparation method of magnetic fluorescent photonic crystal is as follows:
[0138] Superparamagnetic ferroferric oxide nanoparticles are dispersed in a prepolymer solution consisting of hydroxyethyl methacrylate (HEMA), acrylic acid (AA), crosslinking agent ethylene glycol dimethacrylate (EGDMA), photoinitiator 2-hydroxy-2-methyl-1-phenylpropanone (HMPP), ethylene glycol and water, the concentration of HEMA monomer is 0.205 mmol / ml, the concentration of AA monomer is 0.309 mmol / ml, the amount of EGDMA and HMPP is 2% of the total molar amount of HEMA and AA monomers, the concentration of superparamagnetic nanoparticles in the prepolymer solution is 1 mg / ml, and the volume ratio of ethylene glycol to water is 3:1; after irradiating the prepolymer solution with ultraviolet light for 3.5 minutes, it is repeatedly washed with ethanol and centrifuged 2-3 times, and finally the product is dispersed in ethanol.
[0139] The HEMA and AA modified superparamagnetic nanoparticles were mixed evenly with phosphate buffer solution (PBS) and 5-aminofluorescein (AF) in ethanol, PBS accounted for 1% of the whole solution, and the concentration of AF in the solution was 0.035mmol / L. The mixed solution was placed in a 40℃ water bath and stirred overnight to obtain fluorescent modified superparamagnetic nanoparticles. After the reaction, it was washed with ethanol and centrifuged several times. The final product was dispersed in epoxy resin.
[0140] Fig.17 This is the fluorescence spectrum of the product obtained in Example 6. It can be seen from the figure that the product has a relatively obvious fluorescence intensity under an excitation light of a certain wavelength.
[0141] Example 7
[0142] A magnetic fluorescent photonic crystal, comprising a combination of monodisperse core-shell particles and a fluorescent material, wherein the monodisperse core-shell particles are superparamagnetic nanoparticles@polymer layer;
[0143] The superparamagnetic nanoparticles@polymer layer is obtained by mixing superparamagnetic ferroferric oxide nanoparticles, polymer monomers, crosslinking agents, photoinitiators, and dispersion medium solvents to form a prepolymer solution, and then curing it by ultraviolet polymerization in the absence of a magnetic field. The polymer monomers form a polymer that is coated on the surface of the superparamagnetic nanoparticles; the polymer monomers include acrylamide (AM) and acrylic acid (AA), the crosslinking agent is methylene bisacrylamide (BIS), the photoinitiator is 2-hydroxy-2-methyl-1-phenylpropanone (HMPP), and the dispersion medium solvents are ethylene glycol and water; the fluorescent material is trisodium 8-hydroxy-1,3,6-pyrenetrisulfonate.
[0144] Under the action of non-magnetic field, the polymer monomer is coated on the surface of superparamagnetic ferroferric oxide nanoparticles, and the superparamagnetic nanoparticles@polymer layer is provided with carboxyl groups; the fluorescent material is coupled with the superparamagnetic nanoparticles@polymer layer through its own hydroxyl groups.
[0145] The preparation method of magnetic fluorescent photonic crystal is as follows:
[0146] Superparamagnetic ferroferric oxide nanoparticles are dispersed in a prepolymer solution consisting of acrylamide (AM), acrylic acid (AA), crosslinker bisacrylamide (BIS), photoinitiator 2-hydroxy-2-methyl-1-phenylpropanone (HMPP), ethylene glycol and water, the concentration of AM monomer is 0.205 mmol / ml, the concentration of AA monomer is 0.138 mmol / ml, the amount of BIS and HMPP is 2% of the total molar amount of AM and AA monomers, the concentration of superparamagnetic nanoparticles in the prepolymer solution is 0.8 mg / ml, and the volume ratio of ethylene glycol to water is 5:2; after irradiating the prepolymer solution with ultraviolet light for 3.5 minutes, it is repeatedly washed with ethanol and centrifuged 2-3 times, and finally the product is dispersed in ethanol to obtain superparamagnetic nanoparticles@polymer layer.
[0147] The AM and AA modified superparamagnetic nanoparticles (superparamagnetic nanoparticles @ polymer layer) were mixed evenly with trisodium 8-hydroxy-1,3,6-pyrenetrisulfonate in water, and the concentration in the solution was 0.05 mmol / L. The mixture was stirred overnight to obtain fluorescent modified superparamagnetic nanoparticles. After the reaction, the mixture was washed with ethanol and centrifuged several times. The final product was dispersed in epoxy resin.
[0148] Fig.18 This is the fluorescence spectrum of the product obtained in Example 7. From the figure, it can be seen that the product has a relatively obvious fluorescence intensity under an excitation light of a certain wavelength.
[0149] Example 8
[0150] A magnetic fluorescent photonic crystal, comprising a monodisperse core-shell particle and a fluorescent material combination, wherein the monodisperse core-shell particle is a superparamagnetic nanoparticle@silicon dioxide layer
[0151] The superparamagnetic nanoparticles@silica layer is prepared by mixing superparamagnetic ferroferric oxide nanoparticles, a silicon source, a catalyst, and a dispersion medium solvent to form a prepolymer solution, and then, in the absence of a magnetic field, the formed silicon dioxide is coated on the surface of the superparamagnetic ferroferric oxide nanoparticles through hydrogen bonding. The silicon source is tetraethyl orthosilicate (TEOS), the catalyst is ammonia water, and the dispersion medium solvent is ethanol and water. The modified fluorescent material is fluorescein isothiocyanate (FITC) combined with γ-aminopropyltriethoxysilane.
[0152] Under the action of non-magnetic field, silica is coated on the surface of superparamagnetic iron oxide nanoparticles, and the superparamagnetic nanoparticles@silica layer has hydroxyl groups. Silica is coated on the surface of superparamagnetic iron oxide nanoparticles through hydrogen bonding; using a coupling agent as a bridge, the silanol on the surface of silica and the methyl end of the coupling agent are connected through hydrolysis condensation, and the other end is connected to the silica layer and the fluorescent material through the action of the amino-isothiocyanate group.
[0153] The preparation method of magnetic fluorescent photonic crystal is as follows:
[0154] Superparamagnetic ferroferric oxide nanoparticles are dispersed in a prepolymer solution composed of tetraethyl orthosilicate (TEOS), ammonia water, ethanol and water, the volume fraction of TEOS is 4.2%, the volume fraction of ammonia water is 2.5%, the concentration of superparamagnetic ferroferric oxide nanoparticles in the prepolymer solution is 0.8 mg / ml, and the volume ratio of ethanol to water is 5:2; after the prepolymer solution is left to stand at room temperature for 30 minutes, it is repeatedly washed with ethanol and centrifuged 2-3 times, and finally the product is dispersed in ethanol to obtain superparamagnetic nanoparticles@silica layer.
[0155] The silica-coated superparamagnetic nanoparticles were mixed evenly with phosphate buffer solution (PBS) and fluorescein isothiocyanate (FITC) bound to γ-aminopropyltriethoxysilane in ethanol, PBS accounted for 0.96% of the whole solution, and the concentration of FITC in the solution was 0.045mmol / L. The mixed solution was placed in a 40℃ water bath and stirred for 1.5h to obtain fluorescently modified photonic nanochains. After the reaction, the mixture was washed with ethanol and centrifuged several times. The final product was dispersed in epoxy resin.
[0156] Fig.19 This is the fluorescence spectrum of the product obtained in Example 8. It can be seen from the figure that the product has a relatively obvious fluorescence intensity under an excitation light of a certain wavelength.
[0157] Example 9
[0158] A magnetic fluorescent photonic crystal, comprising superparamagnetic nanoparticles modified with tannic acid (superparamagnetic nanoparticle-tannic acid layer complex) and a fluorescent material grafted on the surface;
[0159] The superparamagnetic nanoparticle-tannic acid layer is formed by complexing superparamagnetic ferroferric oxide nanoparticles and tannic acid to form a structure in which tannic acid is coated on superparamagnetic nanoparticles; the tannic acid layer is amino-modified by a coupling agent and connected with the carboxyl group of the fluorescent material.
[0160] The preparation method of magnetic fluorescent photonic crystal is as follows:
[0161] Superparamagnetic ferroferric oxide nanoparticles and prepared tannic acid solution were mixed in ethanol at a mass ratio of 5:1. Tannic acid was modified on the surface of superparamagnetic nanoparticles by ultrasound. After the reaction, the particles were washed with ethanol and centrifuged 2-3 times. The final product was dispersed in ethanol.
[0162] The tannic acid-modified particles were mixed evenly with borate buffer solution (BBS) and 5-carboxyfluorescein (5-FAM) bound to N-β (aminoethyl)-γ-aminopropyltrimethoxysilane in ethanol, with BBS accounting for 0.43% of the entire solution and the concentration of 5-FAM in the solution being 0.086 mmol / L. The mixture was stirred overnight to obtain fluorescence-modified photonic nanochains. After the reaction, the particles were washed with ethanol and centrifuged several times, and the final product was dispersed in epoxy resin.
[0163] Fig. 20 This is the fluorescence spectrum of the product obtained in Example 9. From the figure, it can be seen that the product has a relatively obvious fluorescence intensity under an excitation light of a certain wavelength.
[0164] Example 10
[0165] A magnetic fluorescent photonic crystal comprises a combination of monodisperse core-shell particles and a fluorescent material, wherein the monodisperse core-shell particles are superparamagnetic nanoparticles@polymer layer.
[0166] The superparamagnetic nanoparticles@polymer layer is obtained by mixing superparamagnetic ferroferric oxide nanoparticles, polymer monomers, crosslinking agents, photoinitiators, and dispersion medium solvents to form a prepolymer solution, and then curing it by ultraviolet polymerization under the action of a non-magnetic field, and the polymer monomers form a polymer that is coated on the surface of the superparamagnetic nanoparticles; wherein the polymer monomers include hydroxyethyl methacrylate (HEMA) and acrylic acid (AA), the crosslinking agent is ethylene glycol dimethacrylate (EGDMA), the photoinitiator is 2-hydroxy-2-methyl-1-phenylpropanone (HMPP), the dispersion medium solvents are ethylene glycol and water, and the fluorescent material is trisodium 8-hydroxy-1,3,6-pyrenetrisulfonate.
[0167] Under the action of non-magnetic field, the polymer monomer is coated on the surface of superparamagnetic ferroferric oxide nanoparticles, and the fluorescent material is adsorbed on the surface of superparamagnetic nanoparticles@polymer layer through hydrogen bonding.
[0168] The preparation method of magnetic fluorescent photonic crystal is as follows:
[0169] Superparamagnetic ferroferric oxide nanoparticles were dispersed in a prepolymer solution consisting of hydroxyethyl methacrylate (HEMA), acrylic acid (AA), crosslinker ethylene glycol dimethacrylate (EGDMA), photoinitiator 2-hydroxy-2-methyl-1-phenylpropanone (HMPP), ethylene glycol and water. The concentration of HEMA monomer was 0.205 mmol / ml, the concentration of AA monomer was 0.138 mmol / ml, the amount of EGDMA and HMPP was 2% of the total molar amount of AM and AA monomers, the concentration of superparamagnetic nanoparticles in the prepolymer solution was 0.8 mg / ml, and the volume ratio of ethylene glycol to water was 5:2. After the prepolymer solution was irradiated with ultraviolet light for 5 minutes, it was repeatedly washed with ethanol and centrifuged 2-3 times. Finally, the product was dispersed in ethanol to obtain superparamagnetic nanoparticles@polymer layer.
[0170] The superparamagnetic nanoparticles modified with HEMA and AA (superparamagnetic nanoparticles @ polymer layer) were mixed evenly with trisodium 8-hydroxy-1,3,6-pyrenetrisulfonate in ethanol. The concentration in the solution was 0.1mmol / L. The mixed solution was stirred for 1h to obtain superparamagnetic nanoparticles adsorbed by fluorescent materials. After the reaction, the superparamagnetic nanoparticles were washed with ethanol, centrifuged several times, and homogenized by ultrasound. The final product was dispersed in epoxy resin.
[0171] Fig.21 This is the fluorescence spectrum of the product obtained in Example 10. From the figure, it can be seen that the product has a relatively obvious fluorescence intensity under an excitation light of a certain wavelength.
[0172] Embodiment 11
[0173] A magnetic fluorescent photonic crystal, comprising a combination of monodisperse core-shell particles and a fluorescent material, wherein the fluorescent material is in the shell layer, and the monodisperse core-shell particles are superparamagnetic nanoparticles@silicon dioxide layer;
[0174] Superparamagnetic nanoparticles @ silicon dioxide layer with fluorescent material in the shell are prepared by mixing superparamagnetic ferroferric oxide nanoparticles, silicon source, catalyst, fluorescent material and dispersion medium solvent to form a prepolymer solution. In the absence of a magnetic field, the formed silicon dioxide is coated on the surface of the superparamagnetic ferroferric oxide nanoparticles through hydrogen bonding, and the fluorescent material is embedded in the silicon dioxide shell. The silicon source is tetraethyl orthosilicate (TEOS), the catalyst is ammonia water, the fluorescent material is fluorescein isothiocyanate (FITC), and the dispersion medium solvent is ethanol and water.
[0175] The preparation method of magnetic fluorescent photonic crystal is as follows:
[0176] Superparamagnetic ferroferric oxide nanoparticles are dispersed in a prepolymer solution composed of tetraethyl orthosilicate (TEOS), ammonia water, FITC, ethanol and water, wherein the volume fraction of TEOS is 4.2%, the volume fraction of ammonia water is 2.5%, the concentration of FITC in the solution is 0.04 mmol / L, the concentration of superparamagnetic ferroferric oxide nanoparticles in the prepolymer solution is 0.8 mg / ml, and the volume ratio of ethanol to water is 10:1; after the prepolymer solution is stirred at 30°C for 30 minutes, it is repeatedly washed with ethanol and centrifuged 2-3 times to obtain superparamagnetic nanoparticles @ silica layer with fluorescent material in the shell layer, and finally the product is dispersed in epoxy resin.
[0177] Fig. 22 This is the fluorescence spectrum of the product obtained in Example 11. From the figure, it can be seen that the product has a relatively obvious fluorescence intensity under an excitation light of a certain wavelength.
[0178] Example 12
[0179] A magnetic fluorescent photonic crystal comprises a combination of a superparamagnetic nanochain and a fluorescent material, wherein the fluorescent material is in a shell layer and the outer layer of the superparamagnetic nanochain is a silicon dioxide layer.
[0180] The superparamagnetic nanochain with fluorescent material in the shell is prepared by mixing superparamagnetic ferroferric oxide nanoparticles, a silicon source, a catalyst, a fluorescent material, and a dispersion medium solvent to form a prepolymer solution. Under the action of a magnetic field, the formed silicon dioxide is coated on the surface of the superparamagnetic ferroferric oxide nanoparticles through hydrogen bonding, and the fluorescent material is embedded in the silicon dioxide shell and assembled into a one-dimensional chain structure under the action of a magnetic field. The silicon source is tetraethyl orthosilicate (TEOS), the catalyst is ammonia water, the fluorescent material is fluorescein isothiocyanate (FITC), and the dispersion medium solvent is ethanol and water.
[0181] The preparation method of magnetic fluorescent photonic crystal is as follows:
[0182] Superparamagnetic ferroferric oxide nanoparticles are dispersed in a prepolymer solution composed of tetramethyl orthosilicate, ammonia water, FITC, ethanol and water, the volume fraction of TEOS is 4%, the volume fraction of ammonia water is 2%, the concentration of FITC in the solution is 0.04mmol / L, the concentration of superparamagnetic ferroferric oxide nanoparticles in the prepolymer solution is 0.8mg / ml, and the volume ratio of ethanol to water is 10:1; the prepolymer solution is placed at room temperature of 25°C and stirred for 30 minutes, then repeatedly washed with ethanol and centrifuged 2-3 times to obtain superparamagnetic nanochains with fluorescent materials in the shell layer, and finally the product is dispersed in epoxy resin.
[0183] Fig.23This is the fluorescence spectrum of the product obtained in Example 12. From the figure, it can be seen that the product has a relatively obvious fluorescence intensity under an excitation light of a certain wavelength.
[0184] Example 13
[0185] A magnetic fluorescent photonic crystal comprises monodisperse core-shell particles and a fluorescent material mixed with a high-viscosity resin, wherein the monodisperse core-shell particles are superparamagnetic nanoparticles@polymer layer.
[0186] The superparamagnetic nanoparticles@polymer layer is obtained by mixing superparamagnetic ferroferric oxide nanoparticles, polymer monomers, and dispersion medium solvents to form a prepolymer solution, and then thermally polymerizing the polymer monomers under the action of a non-magnetic field to form a polymer coating the surface of the superparamagnetic nanoparticles; the polymer monomers include bisphenol A propylene glycol dimethacrylate (BISGDMA), the dispersion medium solvents are ethanol and water, and the fluorescent material is rhodamine B (RhB). It is dispersed in epoxy resin and mixed with the fluorescent material rhodamine B (RhB) to obtain a magnetic fluorescent photonic crystal.
[0187] The preparation method of magnetic fluorescent photonic crystal is as follows:
[0188] Superparamagnetic ferroferric oxide nanoparticles were dispersed in a prepolymer solution composed of bisphenol A propylene glycol dimethacrylate (BISGDMA), ethanol and water, the concentration of BISGDMA monomer was 0.3 mmol / ml, the concentration of superparamagnetic nanoparticles in the prepolymer solution was 0.65 mg / ml, and the volume ratio of ethanol to water was 10:3; the prepolymer solution was placed in a 30°C water bath and stirred for 30 minutes, then repeatedly washed with ethanol and centrifuged 2-3 times, and finally the product was dispersed in ethanol to obtain superparamagnetic nanoparticles@polymer layer.
[0189] The superparamagnetic nanoparticles coated with BISGDMA were ultrasonically mixed with epoxy resin, and the excess ethanol was dried, wherein the mass fraction of the superparamagnetic nanoparticles coated with BISGDMA in the epoxy resin was 2%; 0.5 ml of RhB was added thereto, and ultrasonically mixed to obtain a magnetic fluorescent photonic crystal.
[0190] Fig.24 The spectrum of the product obtained in Example 13 is compared with that of the optical material not doped with RhB. It can be seen from the figure that after adding RhB, a new peak appears near 600nm. This is the peak position generated by the introduction of the fluorescent material. At the same time, the peak position and intensity of the photonic crystal change slightly.
[0191] Embodiment 14
[0192] A magnetic fluorescent photonic crystal comprises monodisperse core-shell particles and a fluorescent material chemically combined with a high-viscosity resin, wherein the monodisperse core-shell particles are superparamagnetic nanoparticles@polymer layer.
[0193] The superparamagnetic nanoparticle@polymer layer is obtained by mixing superparamagnetic ferroferric oxide nanoparticles, polymer monomers, and a dispersion medium solvent to form a prepolymer solution, and then thermally polymerizing the prepolymer solution under the action of a non-magnetic field. The polymer monomers form a polymer that is coated on the surface of the superparamagnetic nanoparticles. The polymer monomers include bisphenol A propylene glycol dimethacrylate (BISGDMA), and the dispersion medium solvents are ethanol and water.
[0194] A fluorescent material, a buffer solution and an epoxy resin are placed on a magnetic stirrer and stirred to chemically combine the fluorescent material in the epoxy resin matrix, wherein the fluorescent material is 5-aminofluorescein (AF) and the buffer solution is a phosphate buffer solution (PBS) at pH 8.0.
[0195] The preparation method of magnetic fluorescent photonic crystal is as follows:
[0196] Superparamagnetic ferroferric oxide nanoparticles were dispersed in a prepolymer solution composed of bisphenol A propylene glycol dimethacrylate (BISGDMA), ethanol and water, the concentration of BISGDMA monomer was 0.21 mmol / ml, the concentration of superparamagnetic nanoparticles in the prepolymer solution was 0.8 mg / ml, and the volume ratio of ethanol to water was 5:1; the prepolymer solution was placed in a 40°C water bath and stirred for 30 minutes, then repeatedly washed with ethanol and centrifuged 2-3 times, and finally the product was dispersed in ethanol to obtain superparamagnetic nanoparticles@polymer layer.
[0197] 5-aminofluorescein (AF) was added to epoxy resin, and alkaline PBS buffer was added dropwise, and magnetic stirring was carried out overnight, wherein AF accounted for 0.5% of the volume of epoxy resin, and PBS buffer accounted for 1% of the whole. The rotation speed was 400r / min, and the superparamagnetic nanoparticles coated with BISGDMA were dispersed in the epoxy resin combined with AF, and ultrasonic mixing was performed to obtain magnetic fluorescent photonic crystals.
[0198] Fig.25 The fluorescence spectrum of the product obtained in Example 14 shows that the product has a relatively obvious fluorescence intensity under an excitation light of a certain wavelength.
[0199] Embodiment 15
[0200] An optical material of a magnetic fluorescent photonic crystal comprises a prepared magnetic fluorescent photonic crystal (superparamagnetic nanoparticles@silicon dioxide@FITC) and a curable component; the curable component is a resin and a photoinitiator.
[0201] Magnetic fluorescent photonic crystals (superparamagnetic nanoparticles @silicon dioxide @FITC) are prepared according to the scheme of Example 8, dispersed in epoxy resin, and ultrasonically mixed to obtain magnetic fluorescent photonic crystal optical materials, to which photoinitiators are added, and the optical material is placed on a printing layer to obtain a pattern, and the pattern is placed in a magnetic field and irradiated with ultraviolet light to obtain an optical pattern.
[0202] The preparation method of the optical pattern is as follows:
[0203] Epoxy resin was added dropwise to the prepared superparamagnetic nanoparticle@silica@FITC ethanol solution, in which the mass fraction of superparamagnetic nanochains accounted for 2% of the whole solution. After ultrasonic mixing, the solution was placed in an oven to dry the ethanol, thereby obtaining a magnetic fluorescent photonic crystal optical material.
[0204] A photoinitiator is added to the optical material with a mass fraction of 0.5% of the total. After ultrasonic mixing, it is placed on the printing layer and fixed by ultraviolet light to obtain an optical pattern.
[0205] Fig.26 is a spectrum of the optical material obtained in Example 15. When the applied magnetic field changes from 0 to 200 Gs, the peak position gradually blue-shifts, the reflectivity gradually increases, and the reflectivity reaches a maximum value when the magnetic field intensity is 200 Gs; Fig. 27 This is a real picture of the optical pattern obtained in Example 15, where a, b, and c are the intrinsic color, the fluorescent color under ultraviolet irradiation, and the goniochromatic color, respectively. It can be clearly observed from the figure that the goniochromatic color is displayed under natural light and the fluorescent color is displayed under ultraviolet light.
[0206] Example 16
[0207] An optical material of a magnetic fluorescent photonic crystal comprises a prepared magnetic fluorescent photonic crystal (superparamagnetic nanochain @RBITC) and a curable component; the curable component is a resin and a photoinitiator.
[0208] Magnetic fluorescent photonic crystals (superparamagnetic nanochains @RBITC) are prepared according to the scheme of Example 2, dispersed in epoxy resin, and ultrasonically mixed to obtain magnetic fluorescent photonic crystal optical materials. Photoinitiators are added thereto, and the optical material is placed on a printing layer to obtain a pattern. The pattern is placed in a magnetic field and irradiated with ultraviolet light to obtain an optical pattern.
[0209] The preparation method of the optical pattern is as follows:
[0210] Epoxy resin was added dropwise to the prepared superparamagnetic nanochain@RBITC ethanol solution, in which the mass fraction of the superparamagnetic nanochain accounted for 3% of the total. After ultrasonic mixing, the solution was placed in an oven to dry the ethanol, thereby obtaining a magnetic fluorescent photonic crystal optical material.
[0211] A photoinitiator is added to the optical material with a mass fraction of 0.7% of the total. After ultrasonic mixing, it is placed on a printing layer and fixed by ultraviolet light to obtain an optical pattern.
[0212] Fig.28 This is a spectrum of the optical material obtained in Example 16. When the applied magnetic field changes from 0 to 600 Gs, the reflectivity and peak position change only slightly, and the color of the obtained optoelectronic material device in the matrix is better; Fig.29 : is a trend diagram of the color of the optical pattern obtained in Example 16 as the observation angle changes. It can be seen from the figure that when the observation angle increases, the peak position gradually blue-shifts and the reflectivity decreases slightly. The color and intensity of the obtained optical pattern can change reversibly with the change of the observation angle; Fig.30 This is a real picture of the optical pattern obtained in Example 16, where a, b, and c are the intrinsic color, the fluorescent color under ultraviolet irradiation, and the goniochromatic color, respectively. It can be clearly observed from the figure that the goniochromatic color is displayed under natural light and the fluorescent color is displayed under ultraviolet light.
[0213] The above are only preferred specific implementations of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A magnetic fluorescent photonic crystal, characterized in that: It includes a composite and a polymerizable matrix. The magnetic fluorescent photonic crystal is used under magnetic field conditions; the composite includes one or more of a composite of monodisperse core-shell particles and fluorescent materials, a composite of superparamagnetic nanochains and fluorescent materials, monodisperse core-shell particles, and superparamagnetic nanochains; the monodisperse core-shell particles include one or more of superparamagnetic nanoparticles@polymer layer, superparamagnetic nanoparticles@silicon dioxide layer, superparamagnetic nanoparticles@polymer layer@silicon dioxide layer, and superparamagnetic nanoparticles with surface coordination, complexation, or adsorption of polyhydroxy compounds; the superparamagnetic nanochain is a single-chain one-dimensional nanostructure with a silicon dioxide layer and / or a polymer layer as the outer layer and monodisperse magnetic cores arranged at equal intervals inside; When the composite is the monodisperse core-shell particles or superparamagnetic nanochains, the monodisperse core-shell particles or superparamagnetic nanochains are mixed with a polymerizable matrix containing a fluorescent material.
2. The magnetic fluorescent photonic crystal according to claim 1, characterized in that: The superparamagnetic nanoparticles contain at least one element of iron, cobalt and nickel; the particle size of the monodisperse core-shell particles is 60-300nm.
3. The magnetic fluorescent photonic crystal according to claim 1, characterized in that: The magnetic core contains at least one element of iron, cobalt and nickel; the diameter of the superparamagnetic nanochain is 60-300nm.
4. A method for preparing a magnetic fluorescent photonic crystal as claimed in claim 1, characterized in that: The following steps are involved: S1. preparing monodisperse core-shell particles or superparamagnetic nanochains using superparamagnetic nanoparticles and modified materials as raw materials, wherein the modified materials include one or more of polymer monomers, silica precursors, polyhydroxy compounds, and fluorescent materials; S2. Combining the monodisperse core-shell particles or superparamagnetic nanochains with a solution containing a fluorescent material and / or mixing them with a polymerizable matrix containing or not containing a fluorescent material to obtain the magnetic fluorescent photonic crystal.
5. The method for preparing a magnetic fluorescent photonic crystal according to claim 4, characterized in that: The polymer layer formed by the polymer monomer includes polymers or copolymers containing one or more of acrylate groups, polyurethane groups, epoxy groups, and urea groups.
6. The method for preparing a magnetic fluorescent photonic crystal according to claim 4, characterized in that: The step S1 comprises: using superparamagnetic nanoparticles and one or more substances in a solution containing a polymer monomer, a silica precursor, and a fluorescent material as raw materials, inducing polymerization and / or hydrolysis and condensation under the action of a non-magnetic field, so as to obtain superparamagnetic nanoparticles @ polymer layer or superparamagnetic nanoparticles @ polymer layer @ silica layer or superparamagnetic nanoparticles @ silica layer containing / not containing fluorescent materials in the shell layer; the inducing polymerization method comprises ultraviolet polymerization and / or thermal polymerization.
7. The method for preparing a magnetic fluorescent photonic crystal according to claim 4, characterized in that: The step S1 comprises: using superparamagnetic nanoparticles and one or more substances in a solution containing a polymer monomer, a silica precursor, and a fluorescent material as raw materials, inducing polymerization and / or hydrolysis and condensation under the action of a magnetic field, so as to obtain a superparamagnetic nanochain containing / not containing a fluorescent material in the shell; the induced polymerization method comprises ultraviolet polymerization and / or thermal polymerization.
8. The method for preparing a magnetic fluorescent photonic crystal according to claim 4, characterized in that: The step S1 comprises: mixing superparamagnetic nanoparticles with polyhydroxy compounds and subjecting to ultrasound to obtain the superparamagnetic nanoparticles with surface coordination, complexation or adsorption of polyhydroxy compounds.
9. The method for preparing a magnetic fluorescent photonic crystal according to claim 4, characterized in that: In step S2, the combining method is: adding a solution containing fluorescent material to monodisperse core-shell particles or superparamagnetic nanochains to react, thereby obtaining the magnetic fluorescent photonic crystal; the solution containing fluorescent material includes fluorescent material, coupling agent, and buffer solution.
10. The method for preparing a magnetic fluorescent photonic crystal according to claim 4, characterized in that: In step S2, the mixing method is: mixing the polymerizable matrix with monodisperse core-shell particles or superparamagnetic nanochains combined with the fluorescent material, or mixing the polymerizable matrix containing the fluorescent material with monodisperse core-shell particles or superparamagnetic nanochains to obtain the magnetic fluorescent photonic crystal.
11. The method for preparing a magnetic fluorescent photonic crystal according to claim 10, characterized in that: The polymerizable matrix is one or a mixture of epoxy resin, acrylate resin, polyurethane resin, which may or may not contain fluorescent materials.
12. An optical material comprising the magnetic fluorescent photonic crystal according to claim 1.
13. A method for applying the optical material according to claim 12, characterized in that: The method comprises the following steps: obtaining optical patterns of different colors, intensities and styles by controlling the size and direction of the magnetic field of the magnetic fluorescent photonic crystal, and then fixing the pattern by ultraviolet irradiation or heating; the optical pattern can realize structural colors that vary with angles under visible light, and display fluorescent colors under excitation lighting conditions.
Citation Information
Patent Citations
Tumor cell targeting ultrafine magnetic core-shell nanometer material and its preparation method and use
CN106466488A
Method for regulating particle spacing of Fe3O4@PVP@PNIPAM magnetic photonic crystal nano-chain
CN110423305A
Preparation method of monodisperse core-shell particles capable of being magnetically assembled into high-color saturation photonic crystals in oleoresin
CN112920353A
Recoverable and reusable fluorescent sensor and preparation method thereof
CN113109304A